2005
DOI: 10.2465/jmps.100.247
|View full text |Cite
|
Sign up to set email alerts
|

X-ray studies of structural changes in melanophlogite with varying temperature

Abstract: The a and c unit cell dimensions of melanophlogite (MEP) have been determined in the temperature range −50 to 700 °C, showing a different expansion behavior for the low temperature α phase. The c axis length, 2c, which is smaller than a axis length in the α phase, shows a steep rise reaching the value of a at the tetragonal (α) cubic (β) transition temperature at about 65 °C, and then remains nearly constant until about 500 °C, after which contraction occurs. The crystal structures of α MEP (space group = P4 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
28
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 20 publications
3
28
0
Order By: Relevance
“…In addition to the characteristic structural changes referred to above, Nakagawa et al (2005) also noted that the difference Fourier syntheses showed significant negative values at the O atom sites (down to − 0.7 e/Å 3 ), except for the O 3 site, which was surrounded by positive fringes (illustrated later in Fig. 2).…”
Section: Introductionmentioning
confidence: 93%
See 4 more Smart Citations
“…In addition to the characteristic structural changes referred to above, Nakagawa et al (2005) also noted that the difference Fourier syntheses showed significant negative values at the O atom sites (down to − 0.7 e/Å 3 ), except for the O 3 site, which was surrounded by positive fringes (illustrated later in Fig. 2).…”
Section: Introductionmentioning
confidence: 93%
“…On the other hand, the MSD of the Si atoms in MEP at 84 °C is 0.021 Å 2 , when averaged over 46 atoms, which remains similar to the values observed in common silica structures. Based on these characteristic MSD features, Nakagawa et al (2005) concluded that the structural transition in MEP is driven by an atom disorder mechanism.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations